Neutrophils Play an Important Role in Protective Immunity against Coxiella burnetii Infection - Elliott, Alexandra (Infect Immun, 2015)
Coxiella burnetii is an obligate intracellular Gram-negative bacterium that causes the zoonotic disease Q fever. Although Q fever is mainly transmitted by aerosol infection, study of the immune responses in the lung following pulmonary C. burnetii infection is lacking. Neutrophils are considered the first immune cell to migrate into the lung and play an important role in host defense against aerosol infection with microbial pathogens. However, the role of neutrophils in the host defense against C. burnetii infection remains unclear. To determine the role of neutrophils in protective immunity against C. burnetii infection, the RB6-8C5 antibody was used to deplete neutrophils in mice before intranasal infection with C. burnetii. The results indicated that neutrophil-depleted mice developed more severe disease than their wild-type counterparts, suggesting that neutrophils play an important role in host defense against C. burnetii pulmonary infection. We also found that neither CXC chemokine receptor 2 (CXCR2) nor interleukin-17 (IL-17) receptor (IL-17R) deficiency changed the severity of disease following intranasal C. burnetii challenge, suggesting that keratinocyte-derived chemokine and IL-17 may not play essential roles in the response to C. burnetii infection. However, significantly higher C. burnetii genome copy numbers were detected in the lungs of IL-1R(−/−) mice at 14 days postinfection. This indicates that IL-1 may be important for the clearance of C. burnetii from the lungs following intranasal infection. Our results also suggest that neutrophils are involved in protecting vaccinated mice from C. burnetii challenge-induced disease. This is the first study to demonstrate an important role for neutrophils in protective immunity against C. burnetii infection.